2010
DOI: 10.1007/s11214-010-9667-6
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetic Field of the Earth’s Lithosphere

Abstract: The lithospheric contribution to the Earth's magnetic field is concealed in magnetic field data that have now been measured over several decades from ground to satellite altitudes. The lithospheric field results from the superposition of induced and remanent magnetisations. It therefore brings an essential constraint on the magnetic properties of rocks of the Earth's sub-surface that would otherwise be difficult to characterize. Measuring, extracting, interpreting and even defining the magnetic field of the Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 143 publications
(140 reference statements)
1
59
0
1
Order By: Relevance
“…The final resulting model of the lithospheric field is nonetheless of high quality and compares well with other recently released models (e.g. MF7 that is not published but the MF6 is presented in Maus et al (2008); CHAOS-4; Olsen et al, 2010b) as well as older models (see for a review Thébault et al, 2010).…”
Section: Lesur Et Al: Lithospheric Magnetic Field Model Post-procsupporting
confidence: 64%
“…The final resulting model of the lithospheric field is nonetheless of high quality and compares well with other recently released models (e.g. MF7 that is not published but the MF6 is presented in Maus et al (2008); CHAOS-4; Olsen et al, 2010b) as well as older models (see for a review Thébault et al, 2010).…”
Section: Lesur Et Al: Lithospheric Magnetic Field Model Post-procsupporting
confidence: 64%
“…This led in particular to a continuous stream of ever improving models of the lithospheric field (for a recent review, see e.g. Thébault et al 2010), and of the core field, the time variations of which are now monitored with unprecedented accuracy (see e.g. .…”
Section: Ongoing Satellite Missions: øRsted Champ and Sac-cmentioning
confidence: 99%
“…Olsen et al (2010b), and recent reviews providing even more information about the fields produced can be found in e.g. Hulot et al (2007), Jackson and Finlay (2007), , for the core field, Purucker and Whaler (2007), Thébault et al (2010) for the lithospheric field, Manoj et al (2006), Maus (2007b), Kuvshinov (2008) for the field produced within the oceans, Kivelson and Russell (1995), Kelley (2009) for the field of external origin, and Constable (2007), Kuvshinov (2008) for externally induced internal fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a complementary way, Olsen et al (2010b) next describe satellite concepts that have been used, will be used, or could be envisaged for measuring the Earth's magnetic field from space. The way these data can be processed to recover the lithospheric field (Thébault et al 2010) and the time-varying core field ) are next discussed. Although many aspects of short-term core dynamics can now be observed, their interpretation is still lagging and remains the subject of much debate.…”
mentioning
confidence: 99%